Systemic action research: Changing system dynamics to support sustainable change - and Burns, Danny (Action Research)
This article explores the characteristics of systemic action research. It looks at the conceptual underpinnings of systemic action research and explores some of the ways in which it differs from (builds on) other forms of action research. It then explores some of the issues and dilemmas faced by systemic action researchers.